2018
DOI: 10.3390/cells7110197
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Blue Light Induces Down-Regulation of Aquaporin 1, 3, and 9 in Human Keratinocytes

Abstract: The development in digital screen technology has exponentially increased in the last decades, and many of today’s electronic devices use light-emitting diode (LED) technology producing very strong blue light (BL) waves. Long-term exposure at LED-BL seems to have an implication in the dehydration of the epidermis, in the alterations of shape and number of the keratinocytes, and in the aging of the skin. Aquaporins (AQPs) are water membrane channels that permeate both water and glycerol and play an important rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Although it is not yet confirmed, an inflammatory skin disease, erythema toxicum neonatorum characterized with papules or pustules only in infants is supposed to be associated with increased levels of AQP1 in epidermis, dermis, and blood vessels ( Marchini et al, 2003 ; Patel et al, 2017 ). A recent study with keratinocyte cell lines has hypothesized that down-regulation of AQP1, 3, and 9 might be concomitant with the aging of the skin induced by long-term exposure to blue light ( Avola et al, 2018 ).…”
Section: Involvement Of Aquaporins In Non-infectious Diseasesmentioning
confidence: 99%
“…Although it is not yet confirmed, an inflammatory skin disease, erythema toxicum neonatorum characterized with papules or pustules only in infants is supposed to be associated with increased levels of AQP1 in epidermis, dermis, and blood vessels ( Marchini et al, 2003 ; Patel et al, 2017 ). A recent study with keratinocyte cell lines has hypothesized that down-regulation of AQP1, 3, and 9 might be concomitant with the aging of the skin induced by long-term exposure to blue light ( Avola et al, 2018 ).…”
Section: Involvement Of Aquaporins In Non-infectious Diseasesmentioning
confidence: 99%
“…The reported effects of IR can be variable depending on the dose and pattern of IR application . Similarly, the skin's response to Vis is less well documented although Vis‐induced reactive oxygen species (ROS) generation and skin tanning have been reported . As solar radiation is polychromatic, the interaction of all three individual components (UV, IR, and Vis) as well as the effects of combinations of the components warrants further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…7 Concerning cutaneous exposure, it has been shown that blue wavelengths penetrate into the skin 10 and induce both ROS production and cell death. 9,11,12 Recent studies have shown that blue light can also induce DNA damage in keratinocytes 13,14 but the identification of the DNA lesions has been poorly studied.…”
mentioning
confidence: 99%